Molecular Basis of GABA Hypofunction in Adolescent Schizophrenia-Like Animals - Xiaodan Wang; Ying Hu; Wenxin Liu; Yuanyuan Ma; Xi Chen; Ting Xue; Donghong Cui (Neural Plasticity)
Schizophrenia is a neurodevelopmental disorder that NMDA receptor (NMDAR) hypofunction appears centrally involved. Schizophrenia typically emerges in adolescence or early adulthood. Electrophysiological and several neurochemical changes have linked the GABA deficits to abnormal behaviors induced by NMDAR hypofunction. However, few studies have systematically investigated the molecular basis of GABA deficits, especially during adolescence. To address this issue, we transiently administrated MK-801 to mice on PND 10, which exhibited schizophrenia-relevant deficits in adolescence. Slice recording showed reduced GABA transmission and PVI+ hypofunction, indicating GABAergic hypofunction. Cortical proteomic evaluation combined with analysis of single cell data from the Allen Brain showed that various metabolic processes were enriched in top ranks and differentially altered in excitatory neurons, GABAergic interneurons, and glial cells. Notably, the GABA-related amino acid metabolic process was disturbed in both astrocytes and interneurons, in which we found a downregulated set of GABA-related proteins (GAD65, SYNPR, DBI, GAT3, SN1, and CPT1A). They synergistically regulate GABA synthesis, release, reuptake, and replenishment. Their downregulation indicates impaired GABA cycle and homeostasis regulated by interneuron-astrocyte communication in adolescence. Our findings on molecular basis of GABA deficits could provide potential drug targets of GABAergic rescue for early prevention and intervention.